Mycophenolate mofetil and lichen planopilaris: systematic review and meta-analysis. (2nd January 2022) - Mostafa, Niyaz; Phan, Kevin; Smith, Saxon
Abstract: Background: For severe cases of lichen planopilaris (LPP), unresponsive to first line therapy, systemic or potent agents may be required for disease control. There have been several reports of the off-label use of mycophenolate mofetil (MMF) in patients with LPP or have developed adverse effects to initial agents. Methods: A systematic review and meta-analysis was performed according to recommended Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies with ≥5 cases reporting the outcomes of MMF in LPP were pooled and a meta-analysis of proportion was performed. Case reports were excluded from analysis. Results: A total of six studies were identified and included for meta-analysis, comprising 94 LPP patients. The pooled proportion of any good response (partial or complete) was 69.2% (95% confidence interval (CI): 47.8–77). The pooled proportion of complete response was 20% (95% CI: 10.1–36.3). The pooled proportion of partial responses was 49.2% (95% CI: 30.5–63.7). Side effects occurred in 16.9% (95% CI: 17.6–33.2). of cases, which included elevated LFTs, edema, hyperlipidemia, anemia, herpes zoster infection, photosensitivity, and urinary tract infection. Conclusion: The current evidence for MMF remains limited. However, it appears to be a potential treatment option for patients with severe or recalcitrant LPP who have failed hydroxychloroquine and other immunosuppressants.